Morphological and molecular datasets for Kaempferia species - Labrooy, Catherine Dharshini; Abdullah, Thohirah Lee; Stanslas, Johnson (Elsevier, 2018)
This study compared morphological and molecular data for identification of Kaempferia species. Each species was deposited in Institute of Bioscience (IBS), Universiti Putra Malaysia (UPM) as voucher specimens and ITS sequences of each species deposited in NCBI (https://www.ncbi.nlm.nih.gov/) as GenBank accessions. DNA was extracted using a modified CTAB method and PCR amplification was completed using Internal Transcribed Spacer (ITS4 and ITS5) markers. PCR amplification of products were viewed under gel electrophoresis. Sequencing was performed and sequence characteristics of ITS rDNA in Kaempferia is shown. Qualitative and qualitative scoring of morphological characters and measuring techniques for Kaempferia species are included. In addition, a brief review of molecular markers used in phylogenetic studies of Zingiberaceae is included in this dataset.